Haemodynamic Patterns of Severe Aortic Stenosis - A. E. Komlev; M. A. Saidova; T. E. Imaev; V. N. Shitov; R. S. Akchurin (Рациональная фармакотерапия в кардиологии, 2020)
The authors present up-to-date review of clinical pathophysiology of aortic stenosis (AS) based on differentiation of its haemodynamic patterns, and some actual issues of instrumental diagnostics and classification of AS. The variety of clinical presentations of AS is based on diverse combination of pathological changes of haemodynamics. In Russian cardiology, there is no clear pathophysiological classification of AS despite of its relevance under the progress of surgical and transcatheter treatment of AS. The authors suggest the pilot haemodynamic classification of AS which includes 6 types (0-5) based on different combination of the following variables: left ventricle ejection fraction, stroke volume, mean aortic systolic pressure gradient. Severe AS with low transaortic pressure gradient in patients with depressed systolic function of the left ventricle (so called «low flow-low» gradient phenomenon) is referred to as the most frequent, classical haemodynamic pattern of low-gradient AS. The prevalence of this variant is about 10% among European population of patients with severe AS. The inconsistence between aortic valve area and mean pressure gradient is as common as in 35-40% of patients with AS, however, in 30-50% of these cases, AS is not severe. Severe AS is a surgical disease that should be treated in a surgical way in all patients but those in whom predicted risk overbalances potential benefits of the procedure. The use of integrated clinical and instrumental approach for identification of a true sever AS is the matter of great concern, as both overestimation and underestimation can misguide the clinical decision-making process. Verification of severe AS in patients with classical and paradoxical low flow-low gradient AS with specific indications for surgical treatment regarded is further emphasized in the paper. Since transcatheter aortic valve implantation has become a commonly recognized alternative to surgical aortic valve replacement, its role in the treatment of severe AS with different haemodynamic patterns is also discussed. The authors stress on the necessity of using tailored approach for treatment of AS regarding different clinical and pathophysiological scenarios: high gradient AS with preserved ejection fraction, classical and paradoxical low flow-low gradient AS.